(untitled) (The Lumbini Journal of Business and Economics, 2022)
This study examines credit portfolio diversification and firm performance of Nepalese commercial banks. Return on asset and return on equity are selected as the dependent variables. Similarly, real estate loan, term loan, overdraft loan, deprived sector loan, capital adequacy ratio, loan to deposit ratio, and non-performing loan are selected as the independent variables. This study is based on secondary data of 22 commercial banks with 132 observations for the study period from 2015/16 to 2020/21. The data were collected from Banking and Financial statistics published by Nepal Rastra Bank, reports published by Ministry of Finance, the annual report of respective banks and World Bank database. The correlation coefficients and regression models are estimated to test the significance and relationship between credit portfolio diversification and firm performance of Nepalese commercial banks. The study showed that capital adequacy ratio has a positive impact on return on asset. It indicates that increase in capital adequacy ratio leads to increase in return on asset. However, the study also shows that that real estate loan, term loan, overdraft loan, deprived sector loan, and non-performing loan are negative factors that affect return on assets (ROA) of commercial banks in Nepal. It indicates that real estate loan, term loan, overdraft loan, deprived sector loan, and non-performing loan have a negative impact on bank return on assets indicating that higher the real estate loan, term loan, overdraft loan, deprived sector loan, and non-performing loan, lower would be the bank return on assets (ROA). On the other hand, real estate loan and overdraft loan are the positive and significant (at 5% level of significance) factors that affect the return on equity of commercial bank of Nepal. It indicates that increase real estate loan and overdraft loan ratio leads to increase in return on equity. Moreover, the regression result also shows that deprived sector loan and non-performing loan are positive factors that affect the return on equity but the impact is not significant. However, term loan, capital adequacy ratio and loan to deposit ratio has a negative impact on return on equity (ROE) and the result is statistically insignificant.